The Effect Of Cupping On Blood Pressure In Hypertension - Santoso Budi Rohayu; Ketut Wahyudi; Sampari Gerbab IHA (Science Midwifery, 2022)
Pressure blood tall Becomes a problem only when blood pressure is persistent because it makes system circulation and organs that receive blood supply (including heart and brain) tense. one therapy trusted cupping can lower blood pressure. The research objectives are to analyze the effectiveness of cupping to change pressure blood sufferer hypertension. Study this use method study quantitative with type study pre-experimental design. In a study, this is a total of 30 sufferers Coming hypertension went to the clinic house Nur syifa therapy and did not use the drug hypertension. Respondent gets action measurement pressure blood before conducting action cupping. Respondent gets therapy cupping not enough for 3-5 minutes, then measured repeat pressure of the blood after action cupping. Data analysis using the Wilcoxon test. Results show that cupping is effective for lower pressure blood (p-value <0.001), and pressure blood experienced a decrease in average post cupping 1.45 points _ with effect size in the category large (1.0). Therapy cupping is capable lower blood pressure. Future research could compile therapy with other therapies to reduce antihypertensive drugs that cause resistance or affect medicine.